Intima–media complex thickness and carotid atherosclerotic plaque formation in Lublin’s population in the context of selected comorbidities - Tomasz Słomka; Anna Drelich-Zbroja; Magdalena Jarząbek; Małgorzata Szczerbo-Trojanowska (Journal of Ultrasonography, 2018)
Introduction: Atherosclerosis (arteriosclerosis) is a chronic arterial disease of the arteries with chronic inflammatory. The pathology of atherosclerosis is complex, and the atherosclerotic process is multi-factorial, not fully understood. Risk factors of atherosclerotic lesions may include: lipid disorders, hypertension or diabetes. One of the diagnostic methods of discovering atherosclerosis covers the assessment of the intima–media complex thickness by Doppler ultrasonography. Aim: The aim of this report was an evaluation of the relationships between intima–media complex thickness in the right and left carotid arteries and the occurrence of atheromatous plaque in the Lublin population with respect to three possible concomitant medical conditions, mentioned above. Material and methods: A group of 121 subjects was included into the study, all of the participants being residential inhabitants of the Lublin Voivodship. All the participating patients were requested to fill in a questionnaire. After that, the patients were submitted to Doppler sonography concentrated on intima–media complex thickness evaluation. The occurrence of atheromatous plaque was also assessed in obtained sonographic images. Results: There were statistically significant differences for the intima–media complex thickness and for the atheromatous plaque according to all of the reported diseases: hypocholesterolaemia, hypertension and diabetes. Conclusions: The present study confirms that there is a relationship between the thickness of the intima–media complex in the right and left carotid arteries as well as the occurrence of the atherosclerotic plaque regarding the coexistence of specific disease entities in the subjects of the Lublin population.